2011
DOI: 10.1093/annonc/mdq613
|View full text |Cite
|
Sign up to set email alerts
|

Cigar and pipe smoking, smokeless tobacco use and pancreatic cancer: an analysis from the International Pancreatic Cancer Case-Control Consortium (PanC4)

Abstract: This collaborative analysis provides evidence that cigar smoking is associated with an excess risk of pancreatic cancer, while no significant association emerged for pipe smoking and smokeless tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 24 publications
3
49
0
1
Order By: Relevance
“…More recently, the Boffetta-team published a pooled analysis study, where they found no significant association between ST use and pancreatic cancer (Bertuccio et al, 2011). Seen together, these research summaries support an overall conclusion of a low relative risk of any cancer from snus use (Rodu, 2011;Lee, 2011).…”
Section: Perceptions Of Relative Risk Of Disease and Addiction From Cmentioning
confidence: 88%
“…More recently, the Boffetta-team published a pooled analysis study, where they found no significant association between ST use and pancreatic cancer (Bertuccio et al, 2011). Seen together, these research summaries support an overall conclusion of a low relative risk of any cancer from snus use (Rodu, 2011;Lee, 2011).…”
Section: Perceptions Of Relative Risk Of Disease and Addiction From Cmentioning
confidence: 88%
“…Cigar smokers have increased risk for various types of cancers including cancers of the lung and upper aerodigestive tract, pancreas and bladder, as well as for coronary heart disease and chronic obstructive pulmonary disease (6)(7)(8)(9)(10)(11)(12). Cigar smoking is also associated with gum disease and tooth loss (7).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature also supported the fact that smoking cessation can reduce this risk by up to 50%, at all age groups but is particularly important for the prevention of early onset of pancreatic cancer [36]. The cigarette smoke comprises well known sixty carcinogens, that is responsible for the initiation of tumrogenesis [37]. …”
Section: Smokingmentioning
confidence: 96%